PENANGANAN PENGIRIMAN BARANG PAKET REGULER MELALUI UDARA DI PT.INDAH LOGISTIK CARGO - Fitriana Malida Putri; Siti Sofro s (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Handling is a process of action or a way of handling, managing and resolving a case carried out by a freight forwarder so that the case at hand can be controlled and resolved. So handling is a series of work processes for completing cargo when it is received until it is loaded into the aircraft to be transported from one city to another at home and abroad. The purpose of this research is to find out the implementation, constraints and obstacles that occur in handling regular package shipments via air at PT. Indah Logistik Cargo Pekanbaru. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data directly from the field. The key informants of this research are handling, delivery, cargo, speed, timeliness, security. This study uses data collection techniques from literature study, observation, documentation and interviews. The results of this study can be seen that the handling of regular package shipments via air which starts from the completion of documentation, goods security, the collection process to the delivery of goods is going well in accordance with the SOP applied by management and PT. Indah Logistik Cargo, so that the cargo goods sent are still in transit. perfect condition and arrived on time. Keywords : Handling, Air Cargo, Speed, Security, Punctuality, PT. Indah Logistik Cargo